Flavonoids and Isoflavonoids of Millettia dura and Millettia ferruginea: Phytochemical review and chemotaxonomic value - Buyinza, Daniel; Chalo, Duncan Mutiso; Derese, Solomon; Ndakala, Albert; Yenese, Abiy (Biochemical Systematics and Ecology, 2020)
The phytochemical information on Millettia dura Dunn, M. ferruginea (Hochst.) Baker and M. ferruginea subsp. darassana (Cufod.) J.B. Gillett was reviewed. All the three taxa elaborate mainly isoflavones (33 reported), occurring in the flowers, seeds/seed pods, stem bark and root bark. Out of the 33 isoflavones reported, some 19 (ca. 58%) contain prenyl at C-8 or its modification as 2,2-dimethylchromene ring at C-7/C-8, occurring in all the three taxa. Except for three isoflavones isolated from M. ferruginea subsp. darassana, all the isoflavones of these taxa are 5-deoxygenated. In these taxa, oxygenation at C-6 is a common feature, while isoflavones with C-8 oxygenation are rare, only three reported, and all of these from M. dura. There are 7 rotenoids reported from these taxa, and occur almost entirely in the seeds/seedpods of these plants. The major rotenoid with methylenedioxy group at C-2/C-3, millettone and its 12a-hydroxy derivative, millettosine, occur only in M. dura, this appears to distinguish M. dura from M. ferruginea.
Keywords: Millettia dura; Millettia ferruginea; Leguminosae; Isoflavone; Rotenoid; Chemotaxonomy